Critically ill patients' experiences of nursing care and the effect on their personhood: A retrospective study - Ariné Kuyler; Ensa Johnson (Wiley, 2023)
Abstract Aim This study aims to report patients' experiences of nursing care in the critical care unit and the resulting effect of such care on the personhood of patients. Design and Method The study adopted a qualitative design and aimed to include both descriptive and exploratory information. It involved a single participant group comprising ten previously critically ill patients with whom retrospective, semi‐structured interviews were conducted in a natural setting during 2018. Private hospitals in Gauteng, South Africa, were targeted for data collection. Results The findings of this study were categorised and described according to Kitwood's conceptualisation of person‐centred care. Five categories were identified by patients as impacting their personhood and perceived person‐centred care. Conclusion Nurses ability to support perceived personhood of patients during person‐centred care is integral to the betterment of the patient. Patient's experiences of nursing care can often be affected if they perceive their personhood as not being valued by nurses. This study creates increased awareness of these components to ensure that patient‐nurse relationships are established adequately to meet both the patients' and the nurses' needs.